Child Trafficking ... an Analytical Reading of the 1990 African Charter on the Rights and Welfare of the African Child - Dahia, Abdellatif; Meguireche, Mohamed (Journal of Legal Studies and Researches, 2021)
There is no doubt that child trafficking crimes in Africa have witnessed a great development in recent years. Therefore, many measures were taken, including the 1990 African Charter on the Rights and Welfare of the African Child. In this study, we will have an analytical look at the most important provisions of this charter to combat this criminal pattern; we will also shed light on the mechanism for implementing this charter. In conclusion, we present the proposed results and recommendations.